Fault tolerance in wireless sensor networks through self-stabilisation. (1st December 2008) - Turau, V.; Weyer, C.
Wireless sensor networks (WSNs) suffer from resource limitations, high failure rates and faults caused by the lossy nature of wireless communication. This can lead to situations, where nodes lose synchrony and programs reach arbitrary states. Traditional approaches to fault tolerance like fault masking or global resets are not feasible for WSNs. Applying the concepts of self-stabilisation to achieve fault tolerance is a promising concept. However, the majority of self-stabilising algorithms found in the literature is based on models not suitable for WSNs. This paper proposes a problem-independent transformation for algorithms that stabilise under the central daemon scheduler such that they meet the demands of a WSN. Furthermore, a comparison with transformers from the literature is made through a series of simulations. Finally, the proposed transformer is evaluated with a real sensor network in a field test.